A SOCIAL MEDIA AS A TOOL IN DISSEMINATING INFORMATION ON ISLAM AT HIGHER EDUCATIONAL INSTITUTIONS IN BRUNEI DARUSSALAM - Haji Durani, Nurefnazahani Binti (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
ABSTRACT The issue of social media has been largely discussed among the scholars and intellectuals all over the world. There are a lot of strategies and mechanisms have been made by scholars through different ideas and approaches to ensure the authenticity of information on Islam available on social media. During this era of globalization, the Muslim youths have great access to social media in search of information but not all have good knowledge about Islam and able to differentiate or determine the authenticity of information on Islam. It is important for Muslim youths to be guided and attentive towards information posted on social media. The objective of this study is to analyse undergraduate students’ level of awareness and respond towards information on Islam available on social media. Data was gathered by distributing questionnaire to undergraduate students from higher educational institutions in Brunei Darussalam. One of the findings also confirmed on the importance to have a systematic framework created by the government and society as a whole to counter social media threats and issues specifically information on Islam. Keywords: social media, Undergraduate students, Higher educational institutions, information on Islam, Muslim youths